1999
DOI: 10.1016/s8756-3282(99)00190-8
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive relationships of fabric, density, and elastic properties in cancellous bone architecture

Abstract: The hypothesis that trabecular morphology can predict the elastic properties of cancellous bone has only partly been verified and no predictive analytical model is currently available. Such models are becoming increasingly relevant as the resolution levels of three-dimensional scanning techniques approach the size of trabeculae. This study took advantage of micro-finite-element methods and tested the aforementioned hypothesis in normal cancellous bone material collected at six anatomical locations from 56 indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
109
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(113 citation statements)
references
References 33 publications
3
109
1
Order By: Relevance
“…The measures of mechanical anisotropy and the shear moduli showed that the structural anisotropy measures such as MIL1/MIL3 improved the adjusted correlation coefficient significantly. These results in vivo are consistent with results seen in vitro by Ulrich et al [11] and Kabel et al [12]. Using higher-resolution mCT images of specimens of trabecular bone, both groups of investigators found improvements in the finite element derived mechanical properties with the inclusion of structural measures.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The measures of mechanical anisotropy and the shear moduli showed that the structural anisotropy measures such as MIL1/MIL3 improved the adjusted correlation coefficient significantly. These results in vivo are consistent with results seen in vitro by Ulrich et al [11] and Kabel et al [12]. Using higher-resolution mCT images of specimens of trabecular bone, both groups of investigators found improvements in the finite element derived mechanical properties with the inclusion of structural measures.…”
Section: Discussionsupporting
confidence: 87%
“…The directional mechanics of bone may potentially play an important role in predicting biomechanics, as has been shown in vitro [6,11,12], and hence these properties and their relative changes may be useful for fracture prediction and assessing response to therapy. In this study, using a stepwise multiple regression model, we found that App BV/TV clearly explained 73-83% of the variation in elastic moduli and shear moduli, but other measures of bone structure such as App TbSp and TbN increased the adjusted correlation coefficient with the mechanical measures.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,29 Including anisotropy, however, the correlation improves the explanatory capacity further (up to 92%). 10,15,24,30,31,33 Evidently, these results suggest that the value of connectivity density as an additional explanatory variable might be rather limited.…”
Section: Introductionmentioning
confidence: 81%
“…The results of these studies suggest that relative trabecular bone volume in the axial skeleton and lower limbs is significantly lower in modern humans compared with quadrupeds, despite the legs and vertebral column bearing a higher proportion of body mass and peak substrate reaction forces during bipedal locomotion (25)(26)(27). The high positive correlation between BV/TV and bone material properties (28)(29)(30)(31)(32) suggests that trabecular bone in the human lower limb and vertebral column is less stiff than in other primates. Ongoing debates aimed at enhancing our understanding of bone adaptation, skeletal health, and the prevention and treatment of osteoporosis would be greatly enhanced by the determination of the primary factors underlying the relatively gracile skeleton of living humans.…”
mentioning
confidence: 98%